ANALISIS REVIEW JUMLAH TIANG PANCANG (STUDI KASUS PERBEDAAN KEDALAMAN TIANG ANTARA DESIGN DAN PELAKSANAAN) - Teguh Imam Sejati; Topo Hastopo (Jurnal Teknik Indonesia, 2022)
Planning a civil construction cannot be separated from the criteria of safe and economical. Each foundation is required to be able to support the load to the safety limits that has been planned, including supporting the maximum load that may occur. Analysis of the support capacity of the foundation is carried out by paying attention to soil investigation data, the load carried by the foundation, the dimensions of the pile, the distance between the piles and the depth of the pile.In this research, the pile foundation used depth variations to determine the capacity of the pile in withstanding the load of the structure on it. The depth to be analyzed consists of 2 alternative variations, they are 25 meters and 17 meters which is carried out at four locations. The purpose of this study is to find out the bearing capacity comparison of pile foundation based on its depth.The results of the analysis of bearing capacity of the pole group at a depth of 25 m were obtained at each point, amounting to 20019.5 kN at point A1, 25166.3 kN at point P1, 20019.5 kN at points A2 and 25166.2 at points P2. While at a depth of 17 m obtained at each point of 12822.7 kN at point A1, 15321.2 kN at point P1, 10915.1 kN at point A2 and 14864.7 kN at point P2.Keywords: Pile foundation, Bearing capacity, Depth